Rapid Screening of 300 Pesticide Residues in Commercially Available Vegetable-, Fruit-, and Cereal-Based Baby Foods by Using Amino-Functionalized Multiwalled Carbon Nanotubes with QuEChERS and Gas Chromatography-Electrostatic Field Orbitrap High-Resolution Mass Spectrometry - Zhijuan Meng; Sufang Fan; Tongtong Ding; Xiaoxuan Yuan; Limin Zhao; Qiang Li; Yan Zhang (Journal of Food Quality)
A new method for screening 300 pesticide residues in fruit-, vegetable-, and cereal-based baby foods by an improved QuEChERS purification method based on amino-functionalized multiwalled carbon nanotubes (NH2-MWCNTs) combined with gas chromatography-electrostatic field orbitrap high-resolution mass spectrometry (Orbitrap GC-MS) was developed. The samples were extracted with acetonitrile (dry sample soaked in water first for activation), purified by dispersed solid phase extraction (d-SPE) tube modified by NH2-MWCNTs, and detected by Orbitrap GC-MS. Qualitative analysis was carried out by retention time and accurate mass measurements in full scan mode, and external standard method for quantitation was performed using matrix-matched standard calibration, which could effectively eliminate matrix interference. Method validation was performed on commercially available fruit-, vegetable-, and cereal-based baby foods. Good linearity was achieved for 300 pesticides in the concentration range of 5 to 500 μg/kg with correlation coefficients greater than 0.995 0. The limits of detection (LOD) were 0.3–3.0 μg/kg, and the limits of quantification (LOQ) were 1.0–10.0 μg/kg. The average recoveries on 10, 50, and 200 μg/kg spiked levels were in the range of 72.8%–123.4% in three types of samples, with relative standard deviations (RSDs) of 2.0%–13.3%. The proposed method, with simple pretreatment, highly sensitivity, high precision, and accuracy, is suitable for simultaneous analysis of 300 pesticide residues in baby foods. This method provides a reference for accurate screening of low pesticide residues in baby food.